Nonpoint Source Pollution Control Under Incomplete and Costly Information - Y.H. Farzin; J.D. Kaplan (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper analyses the efficient management of nonpoint source pollution (NPS) under limited pollution control budget and incomplete information inherent in NPS pollution. By incorporating information acquisition into a pollution control model, it focuses on the tradeoff between data collection and treatment efforts and derives conditions under which (i) a favourable change in the state of treatment cost at one site may lead to an increase in treatment level at another site, (ii) a higher data collection cost induces more data collection, and (iii) an increase in information productivity leads to an increase in the level of data collection. A numerical simulation of the model illustrates how in managing NPS pollution the value of information acquisition depends on the degree of heterogeneity of polluting sites.
Keywords: D61; D81; D83; Q28; 330; Nonpoint Source Pollution; Uncertainty; Costly information; Constrained pollution control budget; Umweltmanagement; Schutzgebiet; Unvollkommene Information; Informationskosten; Theorie